Suisse Stock Return, Macro Factors, and Efficient Market Hypothesis: Evidence From ARDL Model - Neifar, Malika (Research in Business and Management, 2022)
This study investigates the long-run equilibrium relationship between Suisse stock market (SSM) prices and a set of macroeconomic variables (inflation, interest rate, and exchange rate) using Monthly data for the period 1999:1 to 2018:4. Different specifications and tests will be carried out, namely unit root tests (ADF and PP), Vector Auto Regression (VAR) to select the optimal lag length and for Granger causality and Toda and Yamamoto (TY) Wald non causality testing, VEC Model and (Johansen, 1988)’s test for no cointegration, and ARDL framework and FPSS test of no cointegration hypothesis. Once ECM representation of the ARDL model is used, it confirms temporal causality between (inflation, interest rate, exchange rate) and the stock price. Finding say that there is dynamic short-run adjustment and long-run stable equilibrium relationship between considered macroeconomic variables (except exchange rate) and the stock prices in the SSM. This imply that the SSM is informationally inefficient because publicly available information on macroeconomic variables (inflation and interest rate) can be potentially used in predicting Suisse stock prices.